2019
DOI: 10.1111/1462-2920.14878
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic relationships of uncultured bacteria associated with the microalgae Gambierdiscus

Abstract: Microbial communities inhabit algae cell surfaces and produce a variety of compounds that can impact the fitness of the host. These interactions have been studied via culturing, single-gene diversity and metagenomic read survey methods that are limited by culturing biases and fragmented genetic characterizations. Higher-resolution frameworks are needed to resolve the physiological interactions within these algalbacterial communities. Here, we infer the encoded metabolic capabilities of four uncultured bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 140 publications
2
26
0
Order By: Relevance
“…Further, Alphaproteobacteria-protist associations appeared to be an integral component of the PE and PS biofilms in our study, with both groups frequently detected on these samples. A range of Alphaproteobacteria are known symbionts or pathogens of eukaryotes (Le et al, 2014;Gong et al, 2016) or play important roles in the microbiomes of microalgae (Amin et al, 2012;Kimbrel et al, 2019;Rambo et al, 2019). These typical lifestyle characteristics of Alphaproteobacteria, namely, adaptation to life on the sea surface and associations with protists, point to an opportunistic colonization of microplastics, which is decoupled from an active use of this substratum.…”
Section: Taxonomic Composition Of Plastic Biofilms Is More Strongly Influenced By Location Than By Polymermentioning
confidence: 99%
“…Further, Alphaproteobacteria-protist associations appeared to be an integral component of the PE and PS biofilms in our study, with both groups frequently detected on these samples. A range of Alphaproteobacteria are known symbionts or pathogens of eukaryotes (Le et al, 2014;Gong et al, 2016) or play important roles in the microbiomes of microalgae (Amin et al, 2012;Kimbrel et al, 2019;Rambo et al, 2019). These typical lifestyle characteristics of Alphaproteobacteria, namely, adaptation to life on the sea surface and associations with protists, point to an opportunistic colonization of microplastics, which is decoupled from an active use of this substratum.…”
Section: Taxonomic Composition Of Plastic Biofilms Is More Strongly Influenced By Location Than By Polymermentioning
confidence: 99%
“…However, SM1A02 were also described as facultative aerobic organisms able to metabolize dimethylsulfoniopropionate, an osmolyte produced by several microalgae including O. cf. ovata (Vanucci et al, 2016), as well as sulfated polysaccharides (Deschaseaux et al, 2018;Rambo et al, 2020). Another example is provided by the Alphaproteobacteria consortium, which was already reported as dominant over all the growth phases of O. cf.…”
Section: Associated Microbial Communitiesmentioning
confidence: 93%
“…It has been proposed as a novel anammox (anaerobic ammonia oxidiser) bacterium ( Tian et al 2017 ) found in many activated sludges with good nitrifying performance ( Chen et al 2019 ). It has been also found in the phycosphere of the marine microaglae Gambierdiscus from different locations (Pacific Ocean, Atlantic Ocean, Caribbean Sea), suggesting that it may be broadly associated with this dinoflagellate ( Rambo et al 2019 ). The anaerobic oxidation of ammonium to nitrogen gas appears to be a metabolic pathway present in virtually any anoxic environment where fixed nitrogen (ammonium, nitrate, nitrite) is found.…”
Section: Taxonomic Composition Of the Microbiomementioning
confidence: 99%